The Ufi Gel P (VOCO) aplication for the correction of the resection prosthesis in an orthopaedic rehabilitation of a patient with a postoperative upper jaw defect of oncological origin. Clinical case - Symonenko, Рената Владимировна (Actual Dentistry, 2021)
Summary. The prevalence of malignant neoplasms of the oral cavity occupies a significant place in the structure of oncological diseases while the cancer treatment is mainly complex and radical. Reconstructive surgery is most often associated with removable dentures. The patients after an upper jaw resections take a significant part of patients with postoperative defects. There is still no consensus between the specialists on prosthetics for patients after resection of the upper jaw of oncological origin. The literature shows a large number of problems, the main one is the lack of data on the long-term outcome of the prosthesis of these patients, the «temporality» of the prosthetic constructions and the poor prognosis. From this point of view, the use of high quality elastic materials is a successful for current problems resolution. The work describes the correction method of an upper jaw resection prosthesis by means of an elastic pad. The high-potency of the Ufi Gel P VOCO (Germany), A-silicone based material, was demonstrated for the clinical relining of resection prosthesis in distant future. We succeeded to achieve effective denture adhesion by correcting the peripheral flap along the transitory fold and the A-line with Ufi Gel P elastic material. The elastic correction of resection prosthesis allows to provide emergency help, makes the use of the prosthesis more comfortable, catalyzes the adaptation and has a positive impact on the social rehabilitation of cancer patients.